The Effect of Authentic Leadership on Organizational Citizenship Behaviors Mediated by Trust in Leaders - Ria Wahyuni; Agoes Ganesha Rahyuda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of this study was to analyze the effect of authentic leadership on OCB mediated by trust in leaders at Royal Tulip Springhill Resort Jimbaran. This research was conducted at the Royal Tulip Springhill Resort Jimbaran, the number of samples used was 65 employees using nonprobability sampling with saturated sampling technique. The data were analyzed using path analysis techniques. Collecting data through interviews and distributing questionnaires. The results showed that authentic leadership had a positive and significant effect on OCB at the Royal Tulip Springhill Resort Jimbaran. Authentic leadership has a significant positive effect on trust in leaders of Royal Tulip Springhill Resort Jimbaran. Trust in leaders have a significant positive effect on OCB at Royal Tulip Springhill Resort Jimbaran. Trust in leaders partially mediate the influence of authentic leadership on OCB at Royal Tulip Springhill Resort Jimbaran. The implication of this research is that with the existence of trust in leaders, authentic leadership can have an effect on OCB. Therefore, with better authentic leadership, trust in leaders will increase and will also increase employee OCB.